Ethnomedicinal survey of antidiabetic plants used by six indigenous communities in Sarawak, Borneo - Rajoo, Keeren Sundara; Lepun, Philip; Kayok, Beatrice Lyeja; Umayrah, Nurul Azwany; Abdullah, Nazariena (Elsevier GmbH, 2025)
Introduction: Sarawak, located in one of the planet's most ecologically diverse regions, hosts over 30 distinct sub-ethnic groups, each with its own set of cultural, linguistic, and lifestyle distinctions. This has fostered the development of numerous, unique ethnobotanical traditions. Thus, this study aimed to document the antidiabetic ethnomedicinal knowledge of six indigenous communities and to examine how their cultural practices and beliefs influenced their respective approaches to managing diabetes. Methods: Fieldwork was carried out between 2021 and 2024, engaging 231 herbal medicine practitioners from six Sarawak indigenous groups: Kenyah (n = 24), Melanau Igan (n = 71), Kayan (n = 30), Iban (n = 81), Punan (n = 13), and Baketan (n = 12). Ethnobotanical information was gathered using face-to-face interviews through both unstructured and semi-structured methods. Results: The study documented 34 plant species utilised for diabetes treatment across five of the six communities, with 127 total use-reports. Annona muricata emerged as the most frequently cited species, with 22 use-reports spanning four communities, followed by Orthosiphon aristatus with 14 use-reports from two communities. Substantial differences were noted in traditional knowledge transmission, with rates ranging from 25% in the Kenyah to 91.5% in the Melanau Igan. Plant knowledge similarity between communities ranged from 0% to 35.29%, the highest similarity observed between the Kenyah and Iban. Discussion/Conclusions: This study documents the distribution and transmission of antidiabetic plant knowledge within Sarawak's indigenous populations, with significant variations in species utilisation and knowledge preservation across communities. The quantified differences in knowledge transmission rates and practitioner expertise indicate varying levels of traditional knowledge preservation among the studied groups.